What is the VN role in preventing dental disease in dogs and why is this so important?. Issue 5 (4th May 2019) - Stott, Louise
ABSTRACT: Dental disease is extremely prevalent among dogs and it is essential that it is prevented because it affects health and quality of life. Many factors including breed, genetics, age, weight and systemic diseases can increase the chances of getting dental disease. Owner compliance and a lack of education in dental disease is also a key factor contributing to poor oral health. However, educating owners on the importance of preventing dental disease is crucial to prevention and professional cleaning, daily tooth brushing, dental chews and dry food can all significantly improve dental health.